Predicting success for new flavors with information known pre-launch: a flavored snack food case study - Doan, Alisa R.; Chambers, Edgar, IV (My University, 2012)
Success in the marketplace is the goal of every product launch. Knowing what data to collect before launching a product that could predict success would be valuable to companies. Thus, the objective of this study was to determine whether success of new line extensions for a multi-flavored snack product available internationally could be predicted from information available before launch. Staff from 15 countries completed a questionnaire for each product and included questions related to authenticity, familiarity, and capturing current trends, packaging and market place issues such as product competition and pricing. Using 63 flavors, a discriminant function correctly identified 75.8% successful products as successful and 66.7% unsuccessful products as unsuccessful. Stepwise comparison determined the variables necessary to correctly categorize the snack products: being a trendy flavor, new to the category, based off foods from restaurants or traditional foods. These variables assisted in predicting in market success for this product category.
Keywords: Success; Discriminant analysis; Product development; Stepwise regression